Analisis Kesulitan Belajar Siswa Pada Materi Pokok Hormon Di Kelas XI IPA SMA Negeri 1 Matauli Pandan Tahun Pembelajaran 2016/2017 - Irmayanti, Irmayanti; Hasruddin, Hasruddin; Kartika, Kartika (Jurnal Pendidikan Matematika dan Sains, 2017)
This study aims to determine the difficulties of learning on the subject matter of hormones in class XI IPA SMA Negeri 1 Matauli Pandan Year Learning 2016/2017. The population in this study is all students of class XI IPA SMA Negeri 1 Matauli Pandan consisting of 11 classes with the number of students 324 students. The sample in this study was taken at random as many as 118 students. The methods undertaken in this research are quantitative descriptive. The research instrument uses the data taken with the problem of objective test and questionnaire. From the results of data processing known to have difficulty learning on hormonal material seen from the number of non-completion of students in completing the objective test of 83.05% high categorized. A thorough student has a score below 75 of 98 people given a questionnaire containing questions with 4 indicators of factors that affect student learning outcomes. Based on the result of questionnaire, it can be concluded that the factors that influence the mastery of the most dominant student learning are